Upaya Guru Pendidikan Agama Islam dalam Menumbuhkan Kecerdasan Siswa - Siti Majidah (STAIFAS-Press, 2016)
National Education aims at developing students' potentials in order to become a man of faith and fear of God Almighty, noble, healthy, knowledgeable, skilled, creative, independent and become citizens of a democratic and accountable. However, conditions on the ground there is still a problem. Both from internal and external factors, which in turn affects the behavior of students in the subjects of Islamic religious education, both feats are cognitive, affective and psychomotor. Especially in SMPN 2 Balung that sharpen the intellectual intelligence. The objectives of this research are: Describe the efforts of Islamic religious education teachers in fostering emotional intelligence and spiritual intelligence of students in SMPN 2 Balung. The results of this study stated that the Islamic Education Teachers in Cultivating Emotional Intelligence seeks students by raising various problems that arise in the community through a video display which is then discussed. Inserting knowledge about the importance of communication and concern for others. Foster self-confidence in students through role-playing activities. Train the emotional intelligence of students with the assignment, care and street knowledge. Calligraphy that stimulate the creativity of learners. Istighotsah event held every morning. While efforts Islamic Education Teachers in Cultivating students' spiritual intelligence is to assist students to pray Duha. Award prizes to the students who actively ask. Nurturing students' vision and clear perception that life is a mandate and the realization that man is God and will return to Allah SWT. Kultum after Duha prayer. A source of inspiration by giving examples of good role model to the students or play a video that is inspiring. Keywords: Islamic Education Teachers, Students Intelligence